Effects of health and environmental concerns on choice of public or private transportation - Bazrbachi, Abdullatif (2015)
Klang Valley is the economic nerve center of Malaysia. In 2010 the population in Klang valley reached 6.3 million, and it continue increasing until it reached 7.2 million in 2013. As a result, the transportation sector in this region has grown rabidly, leading to an increase in the level of air pollution constituting up to 68.5% of total air pollution in the country. This study aims to estimate the value of air pollution emitted via transportation in Klang Valley region by focusing on residents who have experienced the current level of air pollution as they contribute to the same via daily commuting choice. In other words, this study focuses on private vehicle drivers who use their vehicles in their daily commuting. To achieve this target, this study used the non-market valuation technique, namely the contingent valuation method (CVM) to estimate Klang Valley residents’ economic value to reduce the current level of air pollution, produced by the vehicle emissions, by estimating their economic value to continue commuting via private vehicles. This generates information on their mean willingness to pay beyond which they might prefer to switch to public transport commuting mode to reduce associated health and environment effect. The result from this study shows that the current private car user are willing to pay as much as RM 4.988 per future daily trip to work, in addition to their current commuting cost to maintain the status-quo. Bid value, Gender, Age, Public transportation efficiency, Health index, and income level were found to be significant in this study. Meanwhile, level of education and the air pollution concerns were founds not to be significant. Moreover, this study adopted the theory of planned behaviour (TPB) to determine the respondents attitudes towards the public transportation system. We found that the majority of the respondents have no positive attitude towards public transportation mode. In addition, we found that 56% of the respondents’ subjective norm (perception about the view of acquaintances) are against and do not support the idea of using public transportation mode. Furthermore, respondents’ “Perceived Behavioural Control” shows that about 46% have enough resources and experiences to voluntarily switch to the use of public transportation. alternative. Finally, we provide an estimation of commuters’ aggregate welfare gain in each of Selangor state and Wilayah Persekutuan state. The aggregate welfare gain respectively computed for these state are equal to RM 3,725,113.02 and RM 12,362,606.8. This finding will aid future policy direction on transport taxing and pricing in reducing the health and environmental impact of air pollution from transportation. Generally, we found that the higher the respondents’ income level, the higher their willingness to pay to maintain the status quo. However, this study does not report the respective economic worth of each attributes associated with private vehicle commuting option. Thus, future research direction on such is recommended for consideration by subsequent studies.